Development of Genomic Simple Sequence Repeat Markers for Evaluating Resources of Armillaira ostoyae and Their Transferability to Armillaira gallica - Sohee Kim; Hwayong Lee (Mycobiology)
In this study, we aimed to develop simple sequence repeat (SSR) markers for evaluating resources in Armillaria ostoyae and examine their transferability to Armillaria gallica, related species. SSR markers were developed using the released A. ostoyae whole-genome sequence (GenBank assembly accession: GCA_900157425.1). The SSR regions were analyzed using the MISA (MIcroSAtellite identification tool) program. A total of 2319 SSR loci consisting of 922 (39.76%) mononucleotide, 763 (32.90%) trinucleotide, and 517 (22.29%) dinucleotide motifs were identified. Marker design involved an arbitrary choice of 150 SSR loci, considering motif abundance. A total of 22 strains of A. ostoyae were analyzed using the developed markers, and 105 markers were successfully amplified. The mean values of major allele frequency, number of alleles, expected heterozygosity, observed heterozygosity, and polymorphism information content (PIC) values were approximately 5.89, 5.4, 0.541, 0.255, and 0.504, respectively. A. gallica was analyzed, and 52 markers (49.5%) were successfully amplified to evaluate the transferability of the developed SSR markers. When these markers were used, the mean values of major allele frequency, number of alleles, expected heterozygosity, observed heterozygosity, and PIC were calculated to be approximately 0.615, 4.3, 0.517, 0.133, and 0.502, respectively. In conclusion, SSR markers were developed using the genome of A. ostoyae, and some of these markers exhibited transferability to A. gallica. These results can be used for resource evaluation of A. ostoyae and A. gallica.